Heart and Liver Defects and Reduced Transforming Growth Factor β2 Sensitivity in Transforming Growth Factor β Type III Receptor-Deficient Embryos - Stenvers, Kaye L. (American Society for Microbiology, 2003)
The type III transforming growth factor β (TGFβ) receptor (TβRIII) binds both TGFβ and inhibin with high affinity and modulates the association of these ligands with their signaling receptors. However, the significance of TβRIII signaling in vivo is not known. In this study, we have sought to determine the role of TβRIII during development. We identified the predominant expression sites of ΤβRIII mRNA as liver and heart during midgestation and have disrupted the murine TβRIII gene by homologous recombination. Beginning at embryonic day 13.5, mice with mutations in ΤβRIII developed lethal proliferative defects in heart and apoptosis in liver, indicating that TβRIII is required during murine somatic development. To assess the effects of the absence of TβRIII on the function of its ligands, primary fibroblasts were generated from TβRIII-null and wild-type embryos. Our results indicate that TβRIII deficiency differentially affects the activities of TGFβ ligands. Notably, TβRIII-null cells exhibited significantly reduced sensitivity to TGFβ2 in terms of growth inhibition, reporter gene activation, and Smad2 nuclear localization, effects not observed with other ligands. These data indicate that TβRIII is an important modulator of TGFβ2 function in embryonic fibroblasts and that reduced sensitivity to TGFβ2 may underlie aspects of the TβRIII mutant phenotype.